Identification of the Global Strategic Trends Defining of Foreign Direct Investments Development - A. V. Tedeeva (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Objectives. The foreign direct investment market is extremely dynamic. This is affected by a large number of factors, both external and internal. On the one hand, corporations change strategic investment priorities due to changes in the volume of accumulated investment resources, technologies used, and the market capacity to which they are oriented. At the same time, transformations take place in the global economy, leading to a change in the external environment, which leads to a change in the conditions for doing business in different countries and industries. The identification, systematization and description of the main strategic trends in the development of the foreign direct investment market and the factors that determine them, therefore, is the research objective of this work.Methods. During the research we used methods of statistical data analysis, scientific generalization, strategic analysis, systematization of scientific approaches.Results. The main indicators of the foreign direct investment market dynamics by countries, regions and international integration unions were analyzed in the framework of this study. As a result, the main global strategic trends in the development of the foreign direct investment market were identified and formulated. It was found that a number of strategic global trends in the development of the foreign direct investment market are sustainable, which determines the need to take them into account when developing appropriate strategies. The results of this study can be used to develop both corporate strategies for the implementation of FDI in certain countries and regions, and in the process of developing national regional and sectoral strategies for investment development.